An analysis of key issues in spa management: viewpoints from international industry professionals. Issue 3 (2nd September 2019) - Smith, Melanie; Wallace, Mike
ABSTRACT: The aim of this paper is to examine the main issues that are pertinent to spa directors and employees when managing a spa. These include spa leadership; employee motivation; customer service; quality management; sustainability; health and safety; marketing and sales; financial management and funding; spa experience design; lifestyle and future trends. Using a sample of 45 in-depth e-interviews with respondents from 17 countries representing different positions within the spa sector, the authors analyse the priorities and challenges highlighted by the interviewees. This is framed by some of the latest studies in spa management, which provide a background and comparison for the primary research.